Correlation of placental pathology with prenatal ultrasound findings. Issue 12 (4th August 2008) - Sebire, N J; Sepulveda, W
Abstract : There have been recent major advances in obstetric ultrasound, regarding both improved technologies and sonographer expertise, which have resulted in changes in antenatal obstetric management. The placenta is routinely examined to some extent at the time of the second trimester fetal anomaly sonogram, timing of delivery in pregnancies complicated by intrauterine growth restriction is primarily dependent on Doppler sonographic assessment of umbilical and uterine artery blood flow, and an increasing number of specific placental lesions have been described. Many non-specialist diagnostic histopathologists may be unfamiliar with these obstetric advances, but they are an increasingly common indication for submission of placentas for histological examination. Since the aims of pathological examination of the placenta are to determine the pathological basis for the clinical findings and advance understanding of the pathophysiology of pregnancy complications, this review therefore provides an overview of the most common prenatal sonographic techniques and their clinical relevance to the diagnostic pathologist, primarily focusing on conditions with specific placental implications. These range from abnormalities of placental site and cord insertion, to obstetric complications such as antepartum haemorrhage, through sonographic placental parenchymal lesions such as subchorionic and intervillous thrombi, or chorioangiomata. In addition, the pathophysiological basis of abnormal maternal and fetal maternal Doppler indices and intrauterine growth restriction are now described, being associated with decidual vasculopathy and villous changes associated with reduced intervillous blood flow respectively. Finally, rare but characteristic, sonographic appearances of villous cystic or hydropic change, may be associated with intrinsic developmental placental abnormalities such as hydatidiform mole and placental mesenchymal dysplasia, which require histological examination for their specific diagnosis.